KUPON BERHADIAH MENURUT TOKOH AGAMA DESA SUNGAI MALAYA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Anshori, Anshori; Syahbudi, Syahbudi; Rahmiani, Nur (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
This study aims to determine the experience of small traders in Sungai Malaya Village in practicing buying and selling with prize coupons and the responses of religious leaders regarding the law related to the practice. This study uses a qualitative method with empirical legal research as the object of the practice of prize coupons in Sungai Malaya Village, Sungai Malaya District, Kubu Raya Regency. Sources of data used primary data in the form of interviews with informants while secondary data in the form of books, journals, theses, and related articles discussing the sale and purchase of prize coupons. While the data collection technique is a field technique. According to the results of the researcher's analysis, it can be concluded that: 1) The practice of gift coupons packaged in the form of rectangular coupons in the Sungai Malaya Village community, Sungai Ambawang District, Kubu Raya Regency is carried out by withdrawing the available coupons and the seller offering attractive prizes. 2) Religious leaders in Sungai Malaya Village, Sungai Ambawang District, Kubu Raya Regency, regarding the prize coupons did not allow this practice because it favored one party, and there was an element of maisir or gambling. 3) Opinions of religious leaders are based on textual concepts (referring to the Qur'an and hadith) and contextual concepts (chance and pure luck).